The Effectiveness of an Intervention Programme for Reducing Peer Rejection in Early Childhood Education - Paula Molinero-González; Luis J. Martín-Antón; Miguel Á. Carbonero-Martín; Wendy L. Arteaga-Cedeño; José Luis Rodríguez-Sáez (MDPI AG, 2023)
In the early years of schooling, peer groups are key to fostering students' overall learning and development. Yet it has been found that around 10% of children suffer from peer rejection in the classroom, with this problem entailing negative consequences both in the short and long term. The problem proves difficult for adults to detect, which usually leads to a delay in measures being taken to intervene and prevent it. This study applies an experimental design with pre-test and post-test measurements in two groups-experimental and control-in order to address the problem of rejection in the early years of schooling. It explores aspects such as sociometric type, degree of victimisation, social and antisocial behaviour, as well as problematic situations among 637 students at six schools. We then implement an intervention programme for socioemotional competence throughout a school year in an effort to improve students' social skills and relationships, focusing specifically on preventing and reducing the rejection experienced by some of these children. The programme comprises 35 teaching activities and strategies that promote the development of competences for student inclusion (curbing aggression, encouraging teamwork, fostering self-esteem, etc.) and that seek to involve all students, teachers, and relatives by offering an array of complementary resources that enrich the initiatives applied (a programme calendar, assessment notebook, questionnaires, related website, material resources). After the intervention programme, it was found that the experimental group had reduced the percentage of students who suffered rejection from 9.9% to 7.3%, although the same was not true of the control group, which went from 9.5% of rejected students to 10.2%. The reduction in the percentage of rejected students in the experimental group after the application of the programme is an encouraging result that invites us to continue working on more comprehensive interventions to prevent and reduce this phenomenon.